2019
DOI: 10.1155/2019/8194310
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Health Status of the Oldest Olds Living on the Greek Island of Ikaria: A Population Based-Study in a Blue Zone

Abstract: Objective To describe the demographic characteristics, socio-economic status, functional status (autonomy, strength), and health status (cognitive and thymic functions, cardiovascular risk factors, and nutritional status) of the oldest olds living on the Greek island of Ikaria. We also try to explain the longevity observed in this population. Methods A cross-sectional observational study of people aged 90 and over living in both municipalities of north-western Ikaria (Evdilos and Raches) was conducted over one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…Taking into consideration that the healthy aging index, used in this study, was developed based on the functionality and mobility theory, our findings suggest that aging Ikarian people are potentially important for their society, since they remain a resource to their families, communities and economies until a very old age. Actually, a recent study on Ikarians also concluded that older Ikarians maintain their functionality and have very few medical conditions, reinforcing the previous statement [ 28 ].…”
Section: Discussionsupporting
confidence: 70%
“…Taking into consideration that the healthy aging index, used in this study, was developed based on the functionality and mobility theory, our findings suggest that aging Ikarian people are potentially important for their society, since they remain a resource to their families, communities and economies until a very old age. Actually, a recent study on Ikarians also concluded that older Ikarians maintain their functionality and have very few medical conditions, reinforcing the previous statement [ 28 ].…”
Section: Discussionsupporting
confidence: 70%
“…From 21 October 2012 to 21 October 2013, we conducted a cross-sectional observational study on potential factors influencing healthy ageing in people aged ≥90 living in Evdilos and Raches, the two municipalities located in the northwestern part of the island, where the longevity has been found to be the highest [ 3 , 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, Poulain and Pes identified a location in Sardinia with exceptional longevity. This region has been designated as a longevity blue zone (LBZ) [ 2 ], a concept that has been defined in a previous study [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations